GENETIC DIVERSITY, HERITABILITY, TRAIT CORRELATION OF HYBRID MAIZE EVALUATED IN TWO CONTRASTING TOPOLOGIES - A. M. Aditya Wardana; Muhammad Azrai; Cri Wahyuni Brahmi Yanti; Roy Effendi; Slamet Bambang Priyanto (UIN Sunan Gunung Djati Bandung, 2026)
Genetic diversity, heritability, and trait relationships are essential parameters for identifying selection criteria and improving maize productivity across diverse growing environments. This study aimed to evaluate genetic diversity, broad-sense heritability, and correlations among agronomic and yield-related traits of hybrid maize cultivated under two contrasting topologies. Field experiments were conducted using hybrid maize genotypes, and data were analyzed through variance component estimation, heritability analysis, and Pearson correlation coefficients. The results showed that phenotypic variance was generally greater than genotypic variance for most traits, indicating a considerable contribution of environmental factors to trait expression. High heritability values were observed for ear height, leaf width, number of kernels per ear, ear length, ear diameter, and shelling percentage, whereas leaf length, moisture content, kernel row number, and thousand-kernel weight exhibited moderate heritability. All observed traits displayed narrow genetic variability, suggesting limited genetic divergence among the evaluated hybrids. Grain yield was positively associated with fresh ear weight, ear length, ear diameter, number of kernels per ear, leaf length, and stem diameter, while flowering time and several vegetative traits tended to show negative associations with yield. Fresh ear weight showed the strongest relationship with grain yield, indicating its importance as a yield-related trait. These findings demonstrate that ear-related characters can be used as reliable indirect selection criteria for yield improvement in hybrid maize.